2002
DOI: 10.1136/vr.151.3.73
|View full text |Cite
|
Sign up to set email alerts
|

Targeted surveillance to assess the prevalence of BSE in high‐risk populations in western France and the associated risk factors

Abstract: A pilot study was set up for the first time in France in August 2000, to obtain more precise estimates on the BSE epidemic in France. Three categories of cattle at risk of BSE (found dead on-farm, euthanased and emergency slaughtered) were sampled exhaustively from August 7 to December 22, 2000, in the three regions assumed to be the most affected with BSE in France (Basse-Normandie, Bretagne and Pays de la Loire). The samples were checked by using Prionics tests, and positive samples were confirmed by Western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 19 publications
2
36
0
1
Order By: Relevance
“…These variables can hence hardly be confounders for the analysis of the trend of the epidemic. This is the reason why we did not include the geographical origin of the animal in the models, even if it is known to be a risk factor [11,20,23]. It helped to keep the study as powerful as possible.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These variables can hence hardly be confounders for the analysis of the trend of the epidemic. This is the reason why we did not include the geographical origin of the animal in the models, even if it is known to be a risk factor [11,20,23]. It helped to keep the study as powerful as possible.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the percentage of BSE cases found either through the Mandatory Reporting System or through the different active surveillance programmes (on fallen stock and at the abattoir) varies with time and space [12,20]. It might be possible that some animals with mild clinical signs were sent to the abattoir, instead of being declared to the mandatory reporting system, since it has been found that about 7% of the animals tested positive at the abattoir had shown some clinical signs suggestive of BSE [7].…”
Section: Population Of Concernmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the largest numbers of tested cattle were healthy slaughtered cattle, the majority of positive cases occurred in the suspected cases and risk populations [29,47,48]. On average throughout the EU, the likelihood of finding BSE cases is more than 20 times higher in the risk populations than in healthy slaughtered cattle.…”
Section: Active Surveillancementioning
confidence: 97%